Public Management Modernization Paths: A Critical Narrative Review of Digital Government and Good Governance - I. I. Shchennikova (Цифровое право, 2025)
Digitalization has not only transformed economy, society and day-to-day routine of individuals, but also has given the government a unique opportunity to keep its sovereignty and power in an ever-changing world provided that the government is open to innovations and digital technologies implementation. Such openness should be confirmed by the willingness to be changed and optimized in order to increase public management efficiency. There are two basic models for optimizing public management: New Public Management and Good Governance. Transfer to a more advanced model of public management — Good Governance — is carried out in parallel with the digitalization of public management and formation of a digital government. The only one way to define the concepts of “digital government”, “Good Governance”, to establish effective legal framework of the relationships in this regard and to identify the reasons why these concepts should be implemented in public management is, on the one hand, to highlight basic principles they are based on, and, on the other hand, to outline essential features of both concepts.